Analysis regarding the fleet and the farm equipment in Romania compared to the European Union - Daniela Nicoleta Bădan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Taking under consideration the fact that the main factor of increasing work productivity, and increasing agricultural production is mechanization, in the present work, I want to analyze the evolution of the farm equipment fleet in Romania and the E.U. during 2010-2016, highlighting the upgrading trend of this sector compared to the demands from the Romanian farmers who buy these equipments from abroad. There are discussions regarding the decreasing of the number of workers in the agricultural sector due to the modernization and the invasion of the market with new models of tractors and equipments that ease the farmer's work by reducing the work hours by half for the same surface compared to the European average.
Keywords: Q16; 330; farm equipments; agricultural flee; share; arable